Simulasi Pemodelan Numerik Hidrodinamika dan Aliran Sedimen pada Bendung PLTA Musi – Bengkulu - Asep Irwan; Dimas Setiya Gunawan; Martin Wahyunus; Hadi Mulyanto (Institut Teknologi Sains Bandung, 2020)
This research aims to identify Hydro-Power Plant (PLTA) sedimentation in Musi-River, Bengkulu, Indonesia. Based on field observation and simulation modeling Surface Modeling System 8.01. High sediment levels cause accumulation of reservoirs and loss of direct storage, which in turn causes loss of production potential for the Musi Hydro-Power Plant, Bengkulu. The data used in this modeling are bathymetry, current velocity of measurement results, water level, and grain size of sediment. Based on field observations, it was found that basic sediment types were dominated by silt and sand. The highest elevated sediment content values of 0.166 gr/l, current velocity in the upstream was 0.54 - 0.61 m/s while the middle section was 0.43 m/s. After the hydrodynamic model is carried out, then the sedimentation model has values that vary throughout the area model, this is influenced by several factors, one of which is the current movement that can affect the amount of water bottom friction. Volume of sediments obtained in the weirs at the PLTA Musi is 211,588 m3 during the simulation of 1 month if multiplied in 1 year, then it obtained 2539,056 m3. From the results of this research, PLTA Musi must prevent this sedimentation bymaking sediment traps in the upstream.